Petrophysical properties and Reservoir modeling of Mishrif Formation at Tuba Field, Southern Iraq - Al-Najm, Fahad; Al-Shahwan, Muwafaq; Al-Beyati, Fawzi (Iraqi Journal of Science, 2023)
Petrophysical properties of Mishrif Formation at the Tuba field determined from interpretation of open log data of(Tu-2,3,4,5,6,12,24,and 25) wells. These properties include total (effected) and secondary porosity, as well as moveable and residual oil saturation into invaded and uninvaded zones. According to Petrophysical properties it is possible to divided Mishrif Formation into three reservoir units (RU1,2,and 3) separated by four cap rocks (Bar1,2,3,and 4) . Three-dimension reservoir model is established by used (Petrel, 2009) Software for each reservoir units. Result shows that the second and third reservoir units represent important reservoir units of Mishrif Formation. Thickness and reservoir properties enhanced toward middle and north part of Tuba oil field, especially, around (Tu-12, 24,25) wells.